The Meaning and Goals of Interreligious Dialogue - Sharma, Arvind (Journal of Dharma, 1983)
Dialogue is "an exchange of ideas or opinions on a particular issue, especially a political or religious issue, with a view to reaching an amicable agreement or settlement". Dialogue is thus something more than conversation. It shares with conversation the elements of exchange of ideas or opinions and an ambience of amiability but is something more than conversation in that it is not quite so freewheeling. It is oriented to issues. At the same time, although it is more than conversation, it is less than participation. Participation involves a greater degree of commitment to joint action than is usually associated with the process of dialogue. Dialogue can, of course, lead to participation.